(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study describes the current state of knowledge and identifies some factors related to knowledge about preventing pressure ulcers among primary caregivers of stroke patients at Nam Dinh General Hospital in 2025. Methods: This is a cross-sectional descriptive study using a convenient sampling method and a pre-designed toolkit. Results: 94.1% of primary caregivers correctly defined pressure ulcers, 86.7% correctly identified factors that promote ulcer development, and 67.4% knew the causes of ulcers. 89.6% of study participants correctly understood the role of the caregiver, 89.6% correctly answered about the appropriate time to change the position of wheelchair users, and only 36.3% of caregivers correctly knew about ulcer prevention diets. Furthermore, 15.5% of caregivers had poor knowledge regarding mobility-related pressure ulcer prevention. The study found a positive correlation between education level and length of care with the primary caregiver's knowledge. Conclusion: Regarding knowledge of preventing pressure ulcers among stroke patients, 71.1% of caregivers met the requirements and 28.9% did not. Educational level and length of care were related to the level of knowledge of caregivers.